United States, Europe, and Asia: Diversity in Nobel Prize-Winning Affiliations - Schlagberger, Elisabeth Maria; Bornmann, Lutz; Bauer, Johann (International Higher Education, 2017)
In 2014, the authors examined all 155 Nobel laureates of the preceding 21 years in physics, chemistry, and physiology/medicine and published the results in the journal Scientometrics. Recently, they extended the analysis to Nobel laureates from 1994 to 2016 (n=170). They focused particularly on the institutions (and countries) the Nobel laureates were affiliated with when they made their decisive research for the prize. They also examined when the Nobel laureates obtained their PhD/M.D. and when the Nobel Prize was awarded.